Self management of type 2 diabetes mellitus patients in Tasikmalaya - Miftahul Falah; Lilis Lismayanti; Nina Pamela Sari; Apep Ibnu Mu’ti (Universitas Muhammadiyah Semarang, 2023)
Diabetes Mellitus (DM) is a non-communicable disease caused by the inability of individuals to manage disease and maintain their health. The aim of this study was to describe the current status of self-management of Diabetes Mellitus patients at Cigeureung Public Health Center, Tasikmalaya City. This research method used Quantitative. The population in this study was 340 people, a total of 57 respondents was recruited by using with simple random sampling technique. Data was collected by the Diabetic Self Management Questionnaire (SMDQ) questionnaire developed by Margentheim Institute for Diabetic Research and univariate analysis was used in this study. The results showed that most self-management was low (38.6%). The conclusion of this study was the majority of respondents' self-management was poor. Therefore, the results of this study can be used as basic information for DM patients to improve their ability to manage their disease independently.